PENGARUH MODEL PEMBELAJARAN KOOPERATIF TIPE TGT (TEAMS GAMES TOURNAMENT) TERHADAP HASIL BELAJAR MATEMATIKA SISWA - Seran, Elizabeth Belavista; Ladyawati, Erlin; Susilohadi, Susilohadi (Universitas PGRI Adi Buana Surabaya, 2018)
This research is motivated by the fact that teaching in schools is more oriented on the activeness of teachers in the learning process and students who do not like learning that menoton. The main task of education is to improve student learning outcomes in schools. The purpose of this research is to know the influence of learning model of TGT (Teams Games Tournament) to the result of learning of class VII students of SMP Jalan Jawa Surabay. This research is a quasy experiment research using posttest only contril design design. The population used in the study were students of class VII C and VII B junior high school in Java junior year 2017/2018. Samples were obtained randomly, class VII-B as control class and class VII-C as experimental class. The research instrument used is a test of student learning outcomes in the form of posttest. The results showed that in the experimental class the average learning outcome was 85.40 while in the control class the average learning outcome was 79.40. It can be seen that there is a difference of the average of learning outcomes, that in the experimental class the average of learning outcomes is higher than the average of control class learning outcomes. On the test t test tcount > ttable with a value of 2.47 > 1.67. So, it can be concluded that there is influence of learning model TGT Teams Games Tournament) to the results of students studying class VII SMP Jalan Jawa Surabaya. Keywords: teams games tornament, cooperative, learning outcomes